A 2023–2024 Literature Review of Validation Standards and Diagnostic Accuracy - Daniele M. Nascimento; Poonam Sharma; Douglas G. Luster (PhytoFrontiers, 2025)
This study evaluated the progress in validating plant pathogen diagnostic assays by comparing recent literature (2023 to 2024) with previous assessments, particularly following the recommendations of Sharma and Luster (2023). Diagnostic accuracy relies on metrics such as analytical and diagnostic specificity, sensitivity, repeatability, and reproducibility, essential for robust diagnostics and effective disease management. Our analysis of recent publications shows increased emphasis on analytical specificity and sensitivity, reflecting improvements, although consistent application of comprehensive validation remains limited. Technologies such as real-time PCR and loop-mediated isothermal amplification (LAMP) continue to be prominent, while emerging methods such as recombinase polymerase amplification (RPA)-CRISPR/Cas12a show potential for rapid, sensitive detection. The findings underscore the need for more uniform validation practices, statistical rigor, and inclusion of all metrics to enhance the reliability, reproducibility, and field utility of diagnostic tools. This continued focus is crucial for advancing plant health management and meeting diverse diagnostic demands. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.